Mutualistic interactions between plants and birds on Kilimanjaro - Vollstaedt, Maximilian; Schleuning, Matthias; Böhning-Gaese, Katrin (Supplement to: Vollstaedt, Maximilian; Ferger, Stefan W; Hemp, Andreas; Howell, Kim M; Böhning-Gaese, Katrin; Schleuning, Matthias (2018): Seed-dispersal networks respond differently to resource effects in open and forest habitats. Oikos, 127(6), 847-854, https://doi.org/10.1111/oik.04703, 2018)
This dataset includes mutualistic interactions between flowering and fruiting plants and all bird and (few) mammal species feeding on these resources. The data was collected on an area of 30 x 100 m on all study plots except for Hel and FEr, where mutualistic interactions could not be observed. All interactions were recorded using direct observations with binoculars following a standardized sampling procedure. Interactions were observed during 25 h distributed over 5 days on each plot.